A glutamatergic basal forebrain to midbrain circuit mediates wakefulness and defensive behavior. (1st May 2022) - Cai, Ping; Chen, Hui-Yun; Tang, Wei-Tao; Hu, Yu-Duan; Chen, Shang-Yi; Lu, Jing-Shan; Lin, Zhi-Hui; Huang, Sheng-Nan; Hu, Li-Huan; Su, Wei-Kun; Li, Qi-Xuan; Lin, Zhi-Jie; et al.
Abstract: Defensive behavior, a group of responses that evolved due to threatening stimuli, is crucial for animal survival in the natural environment. For defensive measures to be timely and successful, a high arousal state and immediate sleep-to-wakefulness transition are required. Recently, the glutamatergic basal forebrain (BF) has been implicated in sleep-wake regulation; however, the associated physiological functions and underlying neural circuits remain unknown. Here, using in vivo fiber photometry, we found that BF glutamatergic neuron is activated by various threatening stimuli, including predator odor, looming threat, sound, and tail suspension. Optogenetic activation of BF glutamatergic neurons induced a series of context-dependent defensive behaviors in mice, including escape, fleeing, avoidance, and hiding. Similar to the effects of activated BF glutamatergic cell body, photoactivation of BF glutamatergic terminals in the ventral tegmental area (VTA) strongly drove defensive behaviors in mice. Using synchronous electroencephalogram (EEG)/electromyogram (EMG) recording, we showed that photoactivation of the glutamatergic BF-VTA pathway produced an immediate transition from sleep to wakefulness and significantly increased wakefulness. Collectively, our results clearly demonstrated that the glutamatergic BF is a key neural substrate involved in wakefulness and defensive behaviors, and encodes these behaviors through glutamatergic BF-VTA pathway. Overexcitation of the glutamatergic BF-VTA pathway may be implicated in clinical psychiatric diseases characterized by exaggerated defensive responses, such as autism spectrum disorders. Highlights: Glutamatergic neurons in the BF responses to various threatening stimuli. Optogenetic activation of BF glutamatergic neurons triggers a range of context-dependent defensive behaviors. Activation of BF glutamatergic terminals in the VTA also strongly promotes defensive behavior. Photoactivating glutamatergic BF-VTA pathway induces transition to wakefulness and increases amount of wakefulness.